Turbot TNFα gene: Molecular characterization and biological activity of the recombinant protein - Ordás, M. Camino; Costa, M. M.; Roca, F. J.; López-Castejón, G.; Mulero, Victoriano; Meseguer, José; Figueras Huerta, Antonio; Novoa, Beatriz (Molecular Immunology, 2007)
12 páginas, 6 figuras, 2 tablas The tumor necrosis factor (TNF) superfamily is composed by several proteins with similar structure and functions. One of the main representatives of this family is TNF-alpha (TNF ), a proinflammatory cytokine which is produced by different immune cells and presents a wide variety of activities. Using the RACE technique, we have cloned and sequenced the turbot TNF cDNA. The analysis of its sequence showed several conserved motifs characteristic of members of the TNF family. A phylogenetic tree constructed with different TNFs of fish and mammals grouped our sequence within the fish TNF cluster. Therefore, the turbot TNF here studied was identified as TNF . The complete TNF gene was obtained by gene walking, and, similarly to the other known fish TNF genes, presented three introns and four exons. A PCR was designed to study the turbot TNF expression in vivo using as stimulus the bacteria Vibrio pelagius strain Hq222 and virus VHSV. The expression of the cytokine happened early after injection, and it was dependent on the pathogen injected and organ analyzed. Virus induced a higher TNF expression, but this response was shorter in time than that induced by bacteria. In addition, TNF expression was in general higher in kidney than in liver, as expected since the former is the haematopoietic organ of fish. The turbot recombinant TNF (rTNF ) was obtained by IPTG induction of bacteria transformed with the pET15b-TNF construct, and it was purified in native conditions. The recombinant protein was approximately 20 kDa in size, and its biological activity was assessed in vitro. No effect of the rTNF neither alone nor in combination with LPS was observed on the chemiluminescence activity of turbot macrophages at any time tested. However, NO production was enhanced by the recombinant protein alone or with LPS 72 h after the addition of the treatments. Finally, turbot rTNF was able to recruit and activate inflammatory cells when injected in gilthead seabream, although to a lesser extent than ...